2006
DOI: 10.1111/j.1365-2036.2006.02949.x
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Rome II‐defined functional constipation in Taiwan and comparison with constipation‐predominant irritable bowel syndrome

Abstract: SUMMARY BackgroundThe epidemiology and impact of functional constipation on Asians remain unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 40 publications
6
38
4
Order By: Relevance
“…However, the findings of the current study do not support the previous research, which reported that lower socioeconomic status and education level were found to be associated with constipation [3, 4, 36, 42, 53, 54]. Furthermore, Suares and Ford [9] indicated that lower socioeconomic status has an impact in increasing the prevalence of functional constipation.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, the findings of the current study do not support the previous research, which reported that lower socioeconomic status and education level were found to be associated with constipation [3, 4, 36, 42, 53, 54]. Furthermore, Suares and Ford [9] indicated that lower socioeconomic status has an impact in increasing the prevalence of functional constipation.…”
Section: Discussioncontrasting
confidence: 99%
“…The prevalence of functional constipation among Asian was up to 14.3% [33–36] whereas it was reported that the pooled prevalence of functional constipation was 11.0% among South East Asian, extracted from a total of 11 studies [9]. To our knowledge, the prevalence rate of functional constipation in Malaysia has not been revealed.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the prevalence of constipation with age in those older than 60 years has been well documented internationally (Chaplin et al, 2000;Hammond, 1964;Harari, Gurwitz, Avorn, Bohn, & Minaker, 1996;Lu, Chang, Chen, Luo, & Lee, 2006;Nakaji et al, 2002;Wong et al, 1999) with some studies indicating that the largest increases occur after 70-75 years of age (McCrea et al, 2009;Talley, Jones, Nuyts, & Dubois, 2003). In addition to increasing age, other risk factors for constipation identified include gender, co-morbidity and medications.…”
Section: Introductionmentioning
confidence: 92%
“…In a study on 1978 individuals over 35 years in Shiraz, southern Iran, Khademolhosseini, et al found no association between IBS and BMI and Liu et al in 2006 also reported no association between FC and alcohol consumption and smoking status. 26,27 Socioeconomic characteristics are an important determinant of health, nutritional status, mortality and morbidity and influence the accessibility, affordability, acceptability, and actual utilization of the available health facilities. 28,29 The Kuppuswamy scale is commonly used to determine the socioeconomic status of an individual based on the overall score of education, occupation of the head of the family and family income per month.…”
Section: Discussionmentioning
confidence: 99%